Personajul masculin sau criza reîntregirii arhetipale / The male character or the archetypal reunification crisis - Nechita, Alina Maria (Swedish Journal of Romanian Studies, 2019)
The outlining of male character traits is an intriguing concern in the literary exegesis and Carmen Dărăbuş manages to combine her passion and her vast knowledge from the philological and psycho-social sphere, to thoroughly and complexly analyze the characters of Romanian and universal texts. By proposing multiple interpretations, the author traces the evolutionary) trajectory of male characters (chronologically speaking), by highlighting the permanent capabilities of metamorphosis of the primordial pattern.